Identification of STN7-associated leaf senescence networks in thylakoid membranes of Arabidopsis - Seongsin Lee; Jihwan Park; Seunghoon Back; Roshan Sharma Poudyal; Dong-Gi Mun; Jingi Bae; Nayoung Gwak; Sang-Won Lee; Daehee Hwang; Yumi Kim (iScience)
Summary: Photosynthetic protein complexes in thylakoid membranes disassemble during leaf senescence, leading to a decline in photosynthetic efficiency. However, the mechanisms by which these protein complexes in chloroplast thylakoid membranes modulate leaf senescence are poorly understood. This study investigated the roles of Arabidopsis thaliana STN7 and STN8 kinases during leaf senescence using proteomic tools, characterizing STN7 and STN8 overexpressors and loss-of-function mutants. During leaf senescence, proteins involved in photosynthesis-associated processes decreased, while those related to lipid metabolism and jasmonic acid–mediated stress responses increased. The abundance and phosphorylation of the thylakoid membrane proteome were regulated by STN7, but not by STN8. Thirty-four STN7 target proteins overlapped with senescence-associated proteins in the wild type, most of which are related to the photosynthetic protein apparatus. Three out of nine mutants defective in STN7 downstream targets (lfnr2, tsp9, and riq2) exhibited accelerated leaf senescence based on chlorophyll a/b ratio measurements and photochemical analyses. Photosynthetic complex formation was normal in all STN7 target protein loss-of-function mutants, indicating the absence of feedback regulation upstream of STN7 during photosynthetic complex assembly. Overall, the data reveal that STN7 is a major kinase component in signaling cascades that link photosynthetic complex formation and leaf senescence.